CURRENT CHALLENGES IN THE CONDITIONS OF DISTANCE EDUCATION: INQUIRY BASED LEARNING - Budnyk, Olena; Protas, Oksana; Voloshchuk, Halyna; Berezovska, Liudmyla; Rusakova, Olha (Revista Inclusiones, 2020)
The article highlights the relevance of using innovative teaching methods by means of modern digital tools and resources. The authors present the pedagogical capabilities of Go-Lab ecosystem (https://www.golabz.eu) for the implementation of Inquiry Based Learning (IBL), digital competence development and critical thinking of students. It is noted that this educational platform today has the largest collection of remote / virtual laboratories, educational applications, more than a thousand research learningenvironments (Inquiry Learning Space –ILS) for distance learning. This is especially relevant in the modern era of the spread of the coronavirus pandemic, because the platform provides interesting resources to motivate students to learn, stimulate their cognitive interests and develop social skills.The advantages of virtual / remote laboratories in working with students, as opposed to traditional learning, including in inclusive education, are described. The stages of a holistic research cycle on the Go-Lab portal are described: orientation, conceptualization, research, conclusions and discussion. Examples of some ILSs for active online experimentation, self-study, development of research skills, group work, etc. are given. Emphasis is placed on the need for teachers to create their own virtual lesson using laboratories and Go-Lab educational applications. The criteria for evaluating the quality of ILS on the Go-Lab portal are presented.